P‐19: Performance Development of Oxide Semiconductor Photodiode with High Work Function Electrode Suitable for Mass Production. Issue 1 (28th June 2022) - Gu, Pengfei; Huang, Jie; Li, Feifei; Huang, Rui; Lu, Yuhang; Xie, Dini; Sun, Hongda; Ning, Ce; Yuan, Guangcai
Abstract : IGZO as the typical representative of oxide semiconductor used for TFT devices, has been widely used in display panel foundary, such as large size OLED, LTPO technology direction. To develop oxide based photodetector (sensor), not only can expand the application direction of oxide semiconductor material, moreover the oxide photodetector integrated with oxide TFT is more convenient. We developed several oxide based vertical MSM photodiode with schottky junction, the IGZO MSM can respond to ultra violet(UV), while new oxide material S1 and S2 can response to blue light. In order to form a schottky junction, metal electrodes materials should have high work function, thus we developed a high work function electrode suitable for mass production, and of witch work function is 4.7eV. In addition, in order to gain the characteristics of diode, the ACT film need be deposited in high oxygen process to prevent form ohm contact. Assisted by TCAD simulation, we researched how to control the oxide schottky junction, including schottky junction, barrier tunneling, to instruct the material selection and electrical properties of control.